2018
DOI: 10.1097/pra.0000000000000316
|View full text |Cite
|
Sign up to set email alerts
|

Is Ketamine the Future Clozapine for Depression? A Case Series and Literature Review on Maintenance Ketamine in Treatment-resistant Depression With Suicidal Behavior

Abstract: Ketamine has shown effectiveness as a rapid-acting antidepressant with antisuicidal effects in terms of reduction of suicidal ideation in the short term. However, the evidence for long-term maintenance ketamine therapy for treatment-resistant depression (TRD) and suicidal behavior is limited. This case series (N=13) highlights the role of adjunctive

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 40 publications
1
9
0
Order By: Relevance
“…Our findings reflect those from case report studies of a similar number of individuals with TRD who were tried on maintenance ketamine therapy, 24,25 which also showed that most patients experienced initial but not ongoing improvement.…”
Section: Discussionsupporting
confidence: 86%
“…Our findings reflect those from case report studies of a similar number of individuals with TRD who were tried on maintenance ketamine therapy, 24,25 which also showed that most patients experienced initial but not ongoing improvement.…”
Section: Discussionsupporting
confidence: 86%
“…Another TRBD patient with psychotic depression and suicidality received a single ketamine infusion as an add-on to lamotrigine 200 mg, olanzapine 25 mg and bupropion 300 mg. The patient’s active suicidal ideation resolved 24 h after ketamine infusion [ 53 ].…”
Section: Resultsmentioning
confidence: 99%
“…There is almost no evidence for an augmented antidepressant effect of ketamine–lamotrigine combination in patients with mood disorders so far. It was observed only in case series and a case report [ 53 , 54 ], but considering the burden of bipolar disorder and the lack of rapid-acting strategies for bipolar depression, there is an urgent need for studies investigating this potentially effective strategy. It is necessary to evaluate the safety of this combination.…”
Section: Discussionmentioning
confidence: 99%
“…Her depressive symptoms partially remitted but she experienced residual cognitive deficits post-ECT which severely impacted her functioning. A previous case series documented her symptomatic remission and significant functional improvement of TRD on intravenous ketamine treatment from 2012-2018 with minimal and transient sideeffects (sedation, nausea and dizziness) that resolved within a week (11). Monthly outpatient maintenance intravenous ketamine was withheld in July 2020 due to concerns about contracting COVID-19 from monthly hospital visits.…”
Section: Case Reportmentioning
confidence: 99%